A miniaturized printed UWB antenna with dual notching for X-b and and aeronautical radio navigation applications - Mohammad Ahmad Salamin; Sudipta Das; B. T. P. Madhav; Soufian Lakrit; Avisankar Roy; Asmaa Zugari (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
A low cost miniaturized UWB microstrip antenna with dual notched band for X band and aeronautical radio navigation (ARN) is presented in this article. The antenna (19 16Ã—"> 25 mm2) is composed of a half-circular ring as a radiation patch with an incomplete ground plane. The measured results indicate a fractional bandwidth of 112% for 16S11â‰¤-"> 10 dB between 3 to 10.6 GHz. The dual notched band has been achieved by incorporating window shaped microstrip closed ring resonators at the rear surface of the designed structure. The first notch band is centered at 7.5 GHz (7 8.1 GHz) to reject interference with X-band downlink (7.25 to 7.74 GHz) and second band centered at 9.1 GHz (8.6 9.4 GHz) to reject interference with aeronautical radio navigation (ARN) (8.7 to 9.2 GHz). The simulated and measured return loss, radiation pattern, and gain shows good agreement which confirms the applicability of the designed antenna for the intended UWB applications.